2011
DOI: 10.1080/09712119.2011.588394
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stocking density and feeding regimen on broilers: performance, carcass traits and bone mineralisation

Abstract: To evaluate the effects of different stocking densities (22.5, 18.75, 15, 11.25, 7.5 broilers/m 2 ) in ad libitum (Al) and limited or pair feeding (Pf) regimens a total of 2550 Ross-308 chicks were taken. All the Pf groups were provided the same amount of feed per broiler, as determined for the Al-fed group with 22.5 broilers/m 2 . Daily weight gain and feed intake were reduced (P5 0.001) as stocking density increased in the Al groups. Feed conversion ratios were worse (P5 0.01) in the Pf groups. Carcass yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
9
2
Order By: Relevance
“…In the present study, tibia Ca and P contents were depressed in the high stocking density group, a fact that suggested the decreased tibia mineralization in this group, leading to a subsequent poor leg health. This was in contrast to previous studies in broilers (Kang, Park, Kim, & Kim, ; Simsek et al., ), where the bone mineral content was not influenced by stocking density. The different examined species might be the cause for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, tibia Ca and P contents were depressed in the high stocking density group, a fact that suggested the decreased tibia mineralization in this group, leading to a subsequent poor leg health. This was in contrast to previous studies in broilers (Kang, Park, Kim, & Kim, ; Simsek et al., ), where the bone mineral content was not influenced by stocking density. The different examined species might be the cause for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Carcass percentage and carcass component ratios were not affected by stocking density. These findings confirmed those of previous studies (Feddes et al, 2002;Simsek et al, 2011). In the present study, inclusion of LE and P in experimental diets did not significantly affect carcass, breast, thighs, abdominal fat, liver and gizzard per cent throughout the experimental period.…”
Section: Discussionsupporting
confidence: 93%
“…In the 2000 report, a critical stocking density for growth depression was estimated around 30 kg/m2, but improved ventilation was suggested to alleviate this effect. Many authors have since reported decreasing growth rates with increasing density (e.g., (de Oliveira et al, 2000;Thomas et al, 2004;Dozier et al, 2005;Dozier et al, 2006;Sirri et al, 2007;Villagra et al, 2009;Beloor et al, 2010;Petek et al, 2010;Sekeroglu et al, 2011;Simsek et al, 2011;Zuowei et al, 2011;Benyi, 2012). The critical density for decreased growth indicated by these studies varied greatly, from as low as 17 kg/m2 (Thomas et al, 2004) to as high as 46 kg/m2 (Dawkins et al, 2004).…”
Section: Stocking Densitymentioning
confidence: 97%
“…Many authors have since reported decreasing growth rates with increasing density (e.g., (de Oliveira et al, 2000;Thomas et al, 2004;Dozier et al, 2005;Dozier et al, 2006;Sirri et al, 2007;Villagra et al, 2009;Beloor et al, 2010;Petek et al, 2010;Sekeroglu et al, 2011;Simsek et al, 2011;Zuowei et al, 2011;Benyi, 2012). Many authors have since reported decreasing growth rates with increasing density (e.g., (de Oliveira et al, 2000;Thomas et al, 2004;Dozier et al, 2005;Dozier et al, 2006;Sirri et al, 2007;Villagra et al, 2009;Beloor et al, 2010;Petek et al, 2010;Sekeroglu et al, 2011;Simsek et al, 2011;Zuowei et al, 2011;Benyi, 2012).…”
Section: Stocking Densitymentioning
confidence: 99%